2011
DOI: 10.1177/1049732311400431
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impact of Epidermolysis Bullosa

Abstract: Epidermolysis bullosa (EB) is a disease in which the skin blisters in response to minimal friction, causing painful wounds. Despite the potentially severe nature of epidermolysis bullosa, research on the psychosocial issues is scarce. The aims of the study were to explore the psychosocial impact of epidermolysis bullosa on affected adults and to identify associated support needs. We collected data using semistructured interviews and employed inductive thematic analysis to organize and analyze them. Three main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 42 publications
0
107
0
6
Order By: Relevance
“…A relatively small number of studies relate to the psychological aspects of living with the disease [2][3][4]. Appreciating the value of medical research, it is worth noting that the progress in therapy is a distant matter whereas people suffering from EB and their families encounter their difficulties now; therefore, it is important to pay attention to their psychical well-being as well.…”
mentioning
confidence: 99%
“…A relatively small number of studies relate to the psychological aspects of living with the disease [2][3][4]. Appreciating the value of medical research, it is worth noting that the progress in therapy is a distant matter whereas people suffering from EB and their families encounter their difficulties now; therefore, it is important to pay attention to their psychical well-being as well.…”
mentioning
confidence: 99%
“…This type of epidermolysis leaves no scars or causes dental changes [1]. Already in junctional EB, cleavage is located in subepidermal Junction, in the lamina lucida [4], producing severe events occurring anemia, growth retardation, hyperkeratosis foot plant, which can be fatal [1].…”
Section: Discussionmentioning
confidence: 99%
“…EB simplex is the most common form (92%), followed by dystrophic EB (5%) and finally the junctional EB (1%). An American study suggested that for every 350 people, one carries a recessive gene for EB congenital [4].…”
Section: Introductionmentioning
confidence: 99%
“…The literature mentions that school children are increasingly conscious of physical differences in relation to their peers. If these perceptions are accompanied by unpleasant comments or mockery, they can make the child feel inferior or undesirable (22,30) …”
Section: Discussionmentioning
confidence: 99%